Microstructural Deformation and the Age of Monazite-(Ce) from Diatectite Granite in the Jarva-Varaka Structure (Kola Region, Russia) - Tatiana Kaulina; Vladimir Shilovskih; Lyudmila Nerovich; Yevgeny Savchenko; Vladimir Bocharov; Lyudmila Lialina; Vadim Il’chenko (Minerals, 2023)
Microstructural deformation and the age of monazite (Ce) from diatectite granite of the presumably impact Jarva-Varaka structure in the Kola Region (northeastern Fennoscandian Shield) are presented. Biotite diatectite granite forms lenses in the aluminous gneisses of the Kola group hosting the 2.5-Ga-layered Jarva-Varaka Massif (JVM). A sample of biotite granite was collected northeast of the Jarva-Varaka Massif near the earlier described pseudotachylitic breccias. BSE images revealed primary domains in monazite grains with rhythmic euhedral zoning and secondary altered domains. Backscattered electron diffraction maps of monazite grains document the development of deformation twins along {100} and {001} and plastically deformed domains with a maximum misorientation of up to 10°. Newly formed areas of recrystallization (neoblasts) cut the twins and plastically deformed domains. Monazite yielded a U-Pb age of 2706 ± 10 Ma (ID-TIMS method), which defines the crystallization age of the host diatectite granite coeval to the 2.76–2.70 Ga metamorphism of the Kola gneisses. A similar age of 2734 ± 139 Ma (ThO2*–PbO isochron) was obtained for primary monazite domains by the chemical U-Th-total Pb isochron method (CHIME). Domains altered under late hydrothermal processes yield CHIME ages of 1796–1723 Ma. Monazite neoblastic domains are close to primary domains in chemical composition and yielded CHIME ages of 2550–2519 Ma, reflecting probably an influence of the JVM formation. The data obtained are insufficient to confirm the impact origin of the Jarva-Varaka structure, which requires further investigation.